Menciptakan Kebijakan Inklusif Dalam Upaya Pengakuan Agama Nenek Moyang di Indonesia: (Studi Kasus Pada Agama Kaharingan di Kalimantan Tengah, Sunda Wiwitan di Jawa Barat, dan Hindu Bali) - Nawangsari, Ertien Rining; Adnin, Hani Nur (Jayapangus Press, 2022)
This research presents a comprehensive analysis of the recognition of ancestral religion in Indonesia, focusing on the challenges and efforts of its adherents to attain official status. The research background involves the legal context of Indonesia, where the 1945 Constitution guarantees religious freedom. However, followers of ancestral religion continue to face stigmatization and legal uncertainty, necessitating this study. The research aims to identify the struggles of ancestral religion adherents, exploring their impacts on social, economic, and identity aspects. Literature and metadata study methods were employed to delve into the challenges faced by these adherents and their efforts to gain recognition, leading to crucial steps such as policy recommendations, community education, and interfaith collaboration to aid ancestral religion followers against discriminatory actions. The research findings depict various negative impacts of the non-recognition of ancestral religion, including difficulties in securing employment and issues related to identity document fulfillment. The efforts of ancestral religion adherents to gain recognition are analyzed in the context of policy recommendations that can improve the existing legal framework. The study's conclusion highlights the urgency of equal recognition for ancestral religion adherents, emphasizing the need for legal and policy reforms to create an inclusive environment. Involving all stakeholders, including the government, religious leaders, and civil society, this research is expected to contribute significantly to the discourse on religious freedom in Indonesia. Therefore, inclusive policy recommendations grounded in local cultural understanding are anticipated to serve as a foundation for positive change in supporting the religious rights of ancestral religion followers in Indonesia.